2003
DOI: 10.1002/ijc.11168
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MMPs by soluble E‐cadherin in human lung tumor cells

Abstract: Loss of E-cadherin/catenin mediated cell-cell adhesion and overexpression of matrix metalloproteinases (MMPs) are largely involved in tumor invasion. It has been recently shown that high levels of a soluble 80 kDa fragment of E-cadherin, resulting from a cleavage by MMPs, are found in serum and in urine from cancer patients. Additionally, this soluble E-cadherin (sE-CAD) promotes cell invasion into chick heart and into collagen type I gels. The aim of our study was to examine the mechanism of sE-CAD-induced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 43 publications
1
97
0
3
Order By: Relevance
“…[32][33][34][35] In a similar fashion, cultured BxPC-3 pancreatic cancer cells, which produce high levels of E-cadherin (data not shown), also constitutively release sE-CAD. Because neither the KLK7 transcript nor hK7 protein could be detected in BxPC-3 cells by RT-PCR or Western analysis (data not shown), respectively, the constitutive release of sE-CAD from this cell line must be dependent on the action of another protease(s) or mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…[32][33][34][35] In a similar fashion, cultured BxPC-3 pancreatic cancer cells, which produce high levels of E-cadherin (data not shown), also constitutively release sE-CAD. Because neither the KLK7 transcript nor hK7 protein could be detected in BxPC-3 cells by RT-PCR or Western analysis (data not shown), respectively, the constitutive release of sE-CAD from this cell line must be dependent on the action of another protease(s) or mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…Motility and invasion of numerous cancer cell types is prevented by expression of the tumour-suppressor E-cadherin. Through its sequestration of the transcriptional co-activator b-catenin, E-cadherin inhibits Tcf/LEF transcriptional activation of numerous targets that contribute to a motile, invasive phenotype, including MT1 (Ara et al, 2000;Takahashi et al, 2002;Nawrocki-Raby et al, 2003a, b;Hazan et al, 2004;Hlubek et al, 2004;Munshi and Stack, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The inability of SKOV-3 and OVCAR-3 cells to invade 3-D collagen gels may relate to their E-cadherin expression (Kokenyesi et al, 2003). That MT1 expression is upregulated through b-catenin signalling may explain the reported inverse correlation between E-cadherin and MT1 expression (Ara et al, 2000;Takahashi et al, 2002;Nawrocki-Raby et al, 2003a, b;Hazan et al, 2004;Hlubek et al, 2004;Munshi and Stack, 2006). Therefore, we analysed cadherin expression to determine whether E-cadherin was associated with the absence of MT1 and cell invasion in SKOV-3 and OVCAR-3 cells.…”
Section: Invasive Capacity Does Not Relate To E-cadherin Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Nectin-4 does not alter the epithelial architecture of Madin-Darby canine kidney cell cysts embedded in a Matrigel matrix (data not shown). Recently, it has been shown that the E-cadherin-shed form was able to increase protease expression and invasive properties of lung tumor cells in vitro (43). Because Nectins are involved in leukocyte transmigration and diapedesis through endothelial cells, we can speculate that soluble Nectin-4 could take part in the process of tumor cell migration and invasion (7).…”
Section: Fig 5 Nectin-4 Cleavage Is Regulated By Tace/adam-17mentioning
confidence: 99%